Virtual OSCE examinations during COVID-19 : A 360 satisfaction assessment from examiners and candidates - Jenkins, Danielle; Nashed, Joseph Y.; Touma, Naji J. (Canadian Urological Association Journal, 2023)
INTRODUCTION: We sought to determine the satisfaction rates of examiners and candidates in a virtual Objective Structured Clinical Exam (OSCE) of graduating Canadian urology residents. METHODS: An annual mock exam, aimed at simulating the licencing urology exam for Canadian graduates, was moved to an online format for the 2020 cohort. This exam consists of an OSCE, and a written multiple-choice exam. The Telemedicine Satisfaction Questionnaire (TSQ), a previously validated tool for clinical encounters with three sub-domains (quality of care provided, similarity to face-to-face encounter, and perception of the interaction) was modified for the purposes of evaluating the OSCE encounter. The TSQ was sent electronically to all examiners and candidates after the exam. RESULTS: There were 14/16 responses from examiners (87.5%) and 24/39 responses from candidates (61.5%). Overall, the format was judged to be a good experience by 13/14 (92.9%) of examiners and 21/24 (87.5%) of candidates; however, when asked specifically if the virtual OSCE was an acceptable way to determine a candidate’s competency to practice urology independently, only 8/14 (57.1%) of examiners and 15/24 (62.5%) of candidates agreed. CONCLUSIONS: This study demonstrates an overall good satisfaction rate among both examiners and candidates when using a teleconference format for a mock OSCE.